2015
DOI: 10.3892/or.2015.3862
|View full text |Cite
|
Sign up to set email alerts
|

OCT4B modulates OCT4A expression as ceRNA in tumor cells

Abstract: OCT4 is an essential transcription factor for maintaining the self-renewal and the pluripotency of embryonic stem cells (ESCs). The human OCT4 gene can generate three mRNA isoforms (OCT4A, OCT4B and OCT4B1) by alternative splicing. OCT4A protein is a transcription factor for the stemness of ESCs, while the function of OCT4B isoforms remains unclear. Most types of cancer express a relatively low level of OCT4 protein, particularly the OCT4B isoforms. In the present study, we found that OCT4A and OCT4B mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 51 publications
2
20
0
1
Order By: Relevance
“…However, the ratio of OCT4A to OCT4B was observed to vary among different cell lines. This could be an important factor for cancer cell biology, since the two variants may influence one another's function; the data provided in the present manuscript supports this claim, as does recent work from other groups (33).…”
Section: Discussionsupporting
confidence: 88%
“…However, the ratio of OCT4A to OCT4B was observed to vary among different cell lines. This could be an important factor for cancer cell biology, since the two variants may influence one another's function; the data provided in the present manuscript supports this claim, as does recent work from other groups (33).…”
Section: Discussionsupporting
confidence: 88%
“…The OCT4 gene has three mRNA isoforms: OCT4A, OCT4B, and OCT4B1. Zheng et al reported that OCT4B functioned as a ceRNA to regulate OCT4A expression in an miRNA-dependent manner in several tumor cell lines [ 45 ]. This is the first report showing spliced gene isoforms serving as ceRNAs.…”
Section: Validated Cernas In Human Cancermentioning
confidence: 99%
“…Though Oct4b differ in their ability to confer self‐renewal as Oct4a (Guo et al, ; Lee et al, ), it may play a role in epithelial‐to‐mesenchymal transition (Papamichos, Lambropoulos, & Kotoula, ). Recent report showed that Oct4b modulated Oct4a expression as competing endogenous RNA (ceRNA) in tumor cells (Li, Yang, et al, ). Human OCT4B1 had a positive correlation with pluripotency (Atlasi et al, ; Papamichos et al, ).…”
Section: Introductionmentioning
confidence: 99%